Comparative study on surgical outcomes of needle port assisted two port laparoscopic appendicectomy verses conventional three-port laparoscopic appendicectomy - Sonarkar, Rajiv; Ghuge, Ashutosh; Akhtar, Murtaza (International Surgery Journal, 2019)
Background: Conventional three port laparoscopic appendicectomy is fast becoming a procedure of choice for appendicitis. Needle port assisted two port laparoscopic appendicectomy is the procedure with similar technique as conventional procedure but has its distinctive advantages. The present study aims to compare the results of needle port assisted two port and conventional three port laparoscopic appendicectomy. Methods: In comparative non-randomized study patients with acute appendicitis, recurrent appendicitis and patients posted for interval appendicectomy of age >18 years, both gender without co-morbidity were enrolled as subjects. Non-consenting patients were excluded. The study factor was needle port assisted two port and conventional three port laparoscopic appendicectomy procedure. The allocation to each procedure was done at random. The outcome factors were compared between both groups. Results: A total of 91 patients with a mean age of 29.77 years and F:M ratio of 1.67:1 were enrolled, of them 31 underwent needle port assisted two port laparoscopic appendicectomy. The mean operative time for two port was 53.38±7.97 min as compared to conventional three port was 44.65±5.86 min which was statistically significant but cosmetic outcome was better as well as statistically significant with two port procedure. The post-operative pain, intra-operative and post-operative complications were compared between these groups but were statistically not significant. Conclusions: Needle port assisted two port laparoscopic appendicectomy appears to give better cosmetic results and can be a good surgical alternative modality for uncomplicated appendicitis.